PENGENALAN BUDAYA NUSANTARA MELALUI PEMBELAJARAN AKSARA ARAB MELAYU DI TPQ JAMIATUL BERKAH - Suwanto; Ratio Maulana Firdaus; Ahmad Ridwan (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The purpose of this study is to describe the efforts to introduce Nusantara culture through learning Arabic-Malay script at TPQ Jamiatul Berkah, Bagan Pete Village, Jambi City. As part of Nusantara's cultural heritage, Arabic-Malay script has deep historical and cultural significance, but is currently increasingly marginalized among the younger generation. This research was conducted using qualitative descriptive methods, through observation, interviews, and documentation techniques. The results show that learning Arabic-Malay script at TPQ Jamiatul Berkah not only functions to improve religious literacy, but also as a means of introducing local cultural identity to students. Through this activity, students are not only able to read and write Arabic-Malay script, but also understand the cultural values ​​inherited in it. Thus, learning Arabic-Malay script plays an important role in preserving Nusantara culture while raising awareness of the younger generation about the importance of maintaining ancestral cultural heritage.